Improvement of the methodology for the property registry formation as a tool preventing the development of hidden monopolies - Pozniakova, Olena (Technology audit and production reserves, 2020)
The paper considers the problem of creating hidden monopolies as a result of concentration of ownership. The object of research is the transformation of ownership and mechanisms for evaluating and monitoring these changes in order to avoid the formation of hidden monopolies. The transformation of ownership is considered as a change in any component of the right of ownership: ownership, use and disposal, since a change in any of these conditions leads to a change in the economic effect of ownership. The features of the functioning of the institution of trust management are considered, it complicates the information base about the ultimate beneficial owners of the existing property registers, in turn, they focus on the right to own property and change the owner. This approach provokes an additional concentration of ownership, is not monitored by state authorities and entails negative socio-economic consequences. The General Property Register proposed in the work provides for the presentation of information on property relations in their dynamics, not only taking into account the right of ownership, but also use and disposal, allows to cover information about the ultimate beneficiaries, previously not always available. A matrix approach is proposed for the formation of the information base of the registry itself, which will be combined into a single database of property relations in the dynamics of both individuals and legal entities. It is assumed that this Register should be formed by the Ministry of Justice of Ukraine. The chronology of property transformation can be recorded from the moment of registration of legal entities and the assignment of the code of the Unified State Register of Enterprises and Organizations of Ukraine, individuals-entrepreneurs and public organizations and the receipt by individuals of an identification code. Information The registry will be available to public authorities that are involved in the planning, disposal, monitoring and evaluation of changes in all forms of ownership from the point of view of public administration. Positive results are expected from the use of the Unified Property Register.